Prevalence and Risk Factors of Advanced Liver Fibrosis in a Population‐Based Study in Germany. Issue 6 (5th February 2022) - Huber, Yvonne; Schulz, Andreas; Schmidtmann, Irene; Beutel, Manfred; Pfeiffer, Norbert; Münzel, Thomas; Galle, Peter R.; Wild, Philipp S.; Lackner, Karl J.; Schattenberg, Jörn M.
Abstract : The prevalence of liver disease, and especially of advanced liver fibrosis, in the German population is poorly defined. The aim of the study was to explore liver enzymes and surrogate scores of hepatic steatosis and advanced hepatic fibrosis in a population‐based cohort study in Germany. In the cross‐sectional population‐based Gutenberg Health study, data of 14, 950 participants enrolled between 2007 and 2012 were captured and analyzed. The distribution of alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma‐glutamyltransferase (GGT), fatty liver index (FLI), and Fibrosis‐4 (FIB‐4) score, as well as the underlying risk factors, were assessed by regression models. Elevated liver enzymes in this population‐based sample were seen in 19.9% for ALT, 12.8% for AST, and 14% for GGT. Risk factors for liver disease included alcohol use and the presence of the metabolic syndrome, which were both risk factors associated with increased liver enzymes. The FLI suggested that 37.5% of the population exhibited hepatic steatosis and 1.1% of patients exhibited a FIB‐4 above the upper cutoff, while 19.2% were in the intermediate range. Interestingly, advanced fibrosis was significantly more frequent in men compared with women (FIB‐4: 1.5% vs. 0.6% [ P < 0.0001]; NFS: 3.6% vs. 1.9% [ P < 0.0001]). In addition, age was a relevant risk factor for exhibiting a noninvasive surrogate score suggestive of advanced fibrosis in the current study population. Conclusion: Elevated liver enzymes were seen in almost a fifth of the German population. At the population‐based level, the prevalence of advanced fibrosis was estimated at 1% in Germany. Abstract : image